Нагота и театральность - Н. Э. Бероян (ՀՀ ԳԱԱ հրատ.)
Զգեստավորումն ինչ-որ բան բացահայտում է և ինչ-որ բան թաքցնում: Դա հասարակական վարքագծի դրսևորում է, որ հատուկ է նաև բեմին: Իսկ մերկությունն արվեստում, ինչպես հայտնի է, էական տեղ է ունեցել սկսած հնագույն ժամանակներից մինչ օրս: The paper considers one of the less studied issues in acting: the expressiveness of nudity in character forming process on stage. The costume shows or hides something. It is the expression of social attitude and typical for the stage. Nudity in art was evaluated and gained the sense at the end of XIX century and at the beginning of XX century.
Keywords: Literature; Language and Literature; PN2000 Dramatic representation; The Theater